Gender Differences in Attitudes Toward Sexual Harassment of Health Care Employees: A Turkish Case Study. Issue 17 (September 2019) - Kara, Derya; Toygar, Sukru Anil
The purpose of the study was to examine differences in sexual harassment attitudes between male and female labor force in health care organizations. A total of 571 employees working in various health care organizations in Turkey participated in the study. Sexual harassment was measured using 22 items and three-factor structure with constructs "Provocative Behavior, " "Normal Flirtations, " and "Trivial Matter" developed by Turgut. The data were collected using percentage, frequency, mean, standard deviation, independent sample t tests, and multivariate analysis of variance and covariance (MANOVA and MANCOVA). The results of the study revealed that a significant gender difference exists in sexual harassment attitudes with respect to "Provocative Behavior" and "Normal Flirtations" factors, while "Trivial Matter" factor was not statistically significant at the probability level of .05 as part of the sexual harassment scale. After controlling for variables such as age, marital status, monthly income level, education level, profession, institution, length of working time in the organization, and length of time in the health care sector; it was seen that most gender differences remained significant.